2017
DOI: 10.1038/s41598-017-09433-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fluid Challenge Decreases Intracellular Volume: A Bioimpedance Spectroscopy-Based Crossover Study in Healthy Volunteers

Abstract: The effects of intravenous fluid therapy on fluid compartments and hemodynamics of the human body remain enigmatic. We therefore tested the efficacy of bioimpedance spectroscopy in a crossover study, where 15 males received 0.5 ml/kg/min ELO-MEL-isoton (osmolarity = 302 mosmol/l) during 60 minutes, or nothing at all. In group “Fluid”, fluid load increased from −0.2 ± 1.0 l extracellular volume at baseline to its maximum of 1.0 ± 0.9 l in minute 70, and remained continuously elevated throughout minute 300. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Secondary study outcomes included laboratory parameters, anthropometric measurements, blood pressure readings, and medications. Bioimpedance spectroscopy‐based assessment of fluid volume status and body composition was performed with the body composition monitor (BCM; Fresenius Medical Care, Bad Homburg, Germany), as previously described . Details on the sample size calculation, OGTT‐derived parameters (including insulin sensitivity and resistance), and BCM measurements are provided in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary study outcomes included laboratory parameters, anthropometric measurements, blood pressure readings, and medications. Bioimpedance spectroscopy‐based assessment of fluid volume status and body composition was performed with the body composition monitor (BCM; Fresenius Medical Care, Bad Homburg, Germany), as previously described . Details on the sample size calculation, OGTT‐derived parameters (including insulin sensitivity and resistance), and BCM measurements are provided in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…A recently introduced equipment called a BCM utilizes a well-established technical solution to assess the absolute volume of the body fluid distribution (ECW, ICW, and TBW) using 50 multiple, discrete frequencies from 3 to 1000 kHz [ 16 ]. Despite the above advantages, the BCM cannot elucidate the changes of IVF and ISF absolute values during HD.…”
Section: Discussionmentioning
confidence: 99%
“…BCM measurement has been recommended that subjects should be resting in a supine position for at least 5 min, before the BCM-measurement is started, such that fluid volume equilibration has taken place [ 14 ]. We measured the various fluid spaces before HD and 1–4 h of HD, and 30 min after HD using a portable, whole-body ankle-to-wrist BIS (BCM; Fresenius AG software version 3.2; Bad Homburg, Germany) [ 16 ] at mid-week (Wednesday–Thursday). The BCM instrument returns measurements on overhydration (OH), TBW, ECW, ICW, urea distribution volume (V urea ) in liters (L).…”
Section: Methodsmentioning
confidence: 99%
“…Infused fluid volumes therefore need to be reduced if R i (ICF) is stable and R 0 (ECF) is trending upward. However, in a recent study, intracellular volume actually decreased (~ 0.8 L over 70 min) upon rapid infusion of intravenous fluid (~ 2 L in ~ 60 min) into healthy male volunteers [ 47 ]. It was suggested that the infusion of fluid was responsible for the increase in ECF.…”
Section: Discussionmentioning
confidence: 99%